2021
DOI: 10.1162/jocn_a_01677
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Templates Are Sharpened through Differential Signal Enhancement, Not Differential Allocation of Attention

Abstract: In visual search, the internal representation of the target feature is referred to as attentional template. The attentional template can be broad or precise depending on the task requirements. In singleton search, the attentional template is broad because the target is the only colored element in the display. In feature search, a precise attentional template is required because the target is in a specific color in an array of varied colors. To measure the precision of the attentional template, we used a cue-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 91 publications
1
9
0
Order By: Relevance
“…Thus, the worse performance at the cued location (i.e., same-location costs) was not caused by attentional suppression of the spatial cue. Rather, Kerzel and Huynh Cong (2021) found that spatial cues resulting in same-location costs reduced subsequent signal enhancement for stimuli at the cued location. Signal enhancement at the cued location is indexed by the CP component (Livingstone et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, the worse performance at the cued location (i.e., same-location costs) was not caused by attentional suppression of the spatial cue. Rather, Kerzel and Huynh Cong (2021) found that spatial cues resulting in same-location costs reduced subsequent signal enhancement for stimuli at the cued location. Signal enhancement at the cued location is indexed by the CP component (Livingstone et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
“…That is, signal enhancement at the cued location may have been selectively inhibited if the spatial cue was in the color of the negative template. The inhibition of signal enhancement may explain why there were pronounced same location costs for nonmatching spatial cues with negative templates (see also Kerzel & Huynh Cong, 2021). Thus, we suggest that negative templates are implemented as a two-stage process where spatial cues are initially attended independently of their color, but subsequent inhibition reduces the signal enhancement at the location of spatial cues in the color of the negative template.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, when searching for a shape singleton target, the shape of the target and the distractor changes unpredictably, which rules out using a feature-specific target template (Lamy et al, 2006). Similarly, in tasks where target and distractor swap colours across trials (Hickey et al, 2006;Theeuwes, 1991;van Moorselaar et al, 2021;Wang & Theeuwes, 2018b) observers cannot use a feature-specific target template (Geng et al, 2017;Kerzel & Huynh Cong, 2020). Under these search conditions, observers adopt a singleton-detection mode (Bacon & Egeth, 1994) to find the target, and down-weighting features or dimensions is no longer a viable strategy for distractor handling.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if the friend you are searching for wears only warm colored shirts, but pants of any color, prioritizing the low-variability distribution of shirt colors over the high-variability distribution of paint colors will maximize predictive information in the target template (i.e., minimize target uncertainty). Target features encoded into working memory are known to be remarkably sensitive to the task-relevance of information (Becker et al, 2010; Boettcher et al, 2020; Geng & Witkowski, 2019; Nobre & Stokes, 2019; Rajsic et al, 2020), and it has been shown that object features are flexibly removed or compressed so that only the most informative features are used to guide attention (Bravo & Farid, 2012, 2016; Kerzel & Cong, 2021; Reeder et al, 2017; Woodman & Vogel, 2008; Zivony & Lamy, 2016). Previous work has also shown that when sensory information differs in reliability, perception is optimally weighted toward the most reliable cue (Fetsch et al, 2012; Hillis et al, 2004), resulting in a “push-pull” dynamic for attentional priority (Foley et al, 2017; Kozyrev et al, 2019; Mehrpour et al, 2020; Pinsk et al, 2004).…”
mentioning
confidence: 99%